Periodization in judo: Winning the European and World championship medals in the same season - Sertic, H.; Segedi, I. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
"The condition of sports form is characterized by extreme specific operating ability and willingness of athletes to achieve the highest sports results. Optimal sports form and high competitive result in a rule must match (Milanovic 2010)". In accordance with the statement that "the number of competitions and financial motivation of top athletes significantly increased (Sikorski 2011)", an extremely important role in the achievement of planned targets for the season has a properly designed plan and training program with a predetermined schedule of sports form (single-cycle or more-cycle periodization). The aim of this study is to determine the number of judoka who won the European Championship (EC) and World Championship (WC) medal in the same season (2001 to 2014) and difference by gender for that parameter. The specific objective is to determine the rank of success of certain categories for Europeans at the Olympic Games (OG), as well as the difference in the number of the male and female from Europe who have won a medal at the Olympics per capita of European participants.